Implementasi Kurikulum Merdeka Belajar Pada Pembelajaran Pendidikan Agama Islam Di Smp 16 Kota Jambi - Jannah, Annisa Roudatun; Hazairin, Indah Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Merdeka Curriculum is a government initiative that aims to improve the quality of education through student-centered learning and character development. However, its implementation in Islamic Religious Education still faces various challenges at the school level. This study aims to describe the implementation of the Merdeka Curriculum in Islamic Religious Education, identify supporting and inhibiting factors, and analyze its impact on students at SMP Negeri 16 Kota Jambi. This study uses a qualitative approach with a field research method. Data were collected through observation, interviews, and documentation involving the principal, Islamic Religious Education teachers, and students. The findings show that the implementation of the Merdeka Curriculum is carried out through the stages of planning, implementation, and evaluation. Supporting factors include teacher creativity and innovation as well as a conducive school environment, while the main inhibiting factor is a lack of family support. The implementation of the Merdeka Curriculum has a positive impact on increasing student involvement and participation and strengthening religious character.